2018
DOI: 10.3311/ppci.11554
|View full text |Cite
|
Sign up to set email alerts
|

Shear Buckling of Plate Girders with Corrugated Web Restrained by End Stiffeners

Abstract: The study reports the investigations into the effect produced by flexural stiffness of end stiffeners on the design buckling resistance of the sine wave webs of girders. Experimental investigations were concerned with load displacement paths in sinusoidally corrugated web girders, composed of structural items and made to the full scale . The phenomena occurring in experimental investigations were represented using the Finite Element Method. In numerical models based on FEM analysis, the same failure modes of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…In girders with corrugated web, intermediate transverse stiffeners are not used to increase shear buckling resistance of the corrugated web because sheet folds, perpendicular to chords, constitute the web stiffening. However, as shown in study [10], support stiffeners mounted at girder ends contribute to resistance increase. Additionally, they affect change in the web failure mode from global to interactive one.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…In girders with corrugated web, intermediate transverse stiffeners are not used to increase shear buckling resistance of the corrugated web because sheet folds, perpendicular to chords, constitute the web stiffening. However, as shown in study [10], support stiffeners mounted at girder ends contribute to resistance increase. Additionally, they affect change in the web failure mode from global to interactive one.…”
Section: Introductionmentioning
confidence: 71%
“…Due to the above, based on investigations reported in [11], it was noted that when intermediate stiffener of the girder having the web height of h w = 500 mm was made from 10 mm thick sheet, shear mode of the web instability always occurred at the intermediate stiffener joint. Next, in the author's studies [10][11][12][13], it was observed that for intermediate stiffener with increased stiffness taking the form of end plate connection of the girder pre-assembled units, the zone of the web shear instability shifted from the intermediate stiffener towards the support. Stiffness of intermediate stiffeners caused the relocation of the corrugated web failure zone.…”
Section: Introductionmentioning
confidence: 99%
“…results in the fact that shear buckling resistance of the corrugated web of SIN girders stated in the code [1] is overestimated. In studies [13,15], it was shown that vertical stiffeners located at the ends of simply supported girders substantially contribute to an increase in shear buckling resistance of the corrugated web. The problem of instability in SIN girders with semirigid and rigid support stiffeners was discussed in study [15].…”
Section: Shear Buckling Resistance Of Cantilever Girders With Corrugamentioning
confidence: 99%
“…In studies [13,15], it was shown that vertical stiffeners located at the ends of simply supported girders substantially contribute to an increase in shear buckling resistance of the corrugated web. The problem of instability in SIN girders with semirigid and rigid support stiffeners was discussed in study [15]. Based on preliminary investigations, it is known that for cantilever girders under two-sided symmetrical load on cantilevers ( Fig.…”
Section: Shear Buckling Resistance Of Cantilever Girders With Corrugamentioning
confidence: 99%
See 1 more Smart Citation